The Association between Psychological Disorders and Heart Failure in Patients with Diabetes Mellitus: A Cross-Sectional Study - Imran Khan, Humaira Rahim, Iftikhar Hussain, Imran Saeed, Hafizuddin, Saeed Maqsood (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Heart failure (HF) is a major complication in patients with diabetes mellitus (DM), and psychological disorders, including depression and anxiety, are common in this population. These psychological conditions may exacerbate the progression and outcomes of heart failure. The aim of this study was to explore the association between psychological disorders and heart failure in patients with diabetes mellitus, examining how these disorders influence heart function, glycemic control, and clinical outcomes. Methods: This cross-sectional study included 130 patients with diabetes mellitus and heart failure. Psychological status was assessed using the Beck Depression Inventory (BDI) for depression and the Generalized Anxiety Disorder (GAD-7) scale for anxiety. Clinical parameters, including left ventricular ejection fraction (LVEF), HbA1c levels, and hospitalization frequency, were recorded. Statistical analysis was performed to assess correlations between psychological disorder severity and clinical outcomes. Results: The study found that 48% of participants had depression, and 41% had anxiety, with significant associations between the severity of these disorders and worse clinical outcomes. Higher depression severity was correlated with lower LVEF (r = -0.45, p < 0.001) and elevated HbA1c levels (r = 0.36, p < 0.01). Anxiety severity was also linked to decreased LVEF (r = -0.39, p < 0.005) and increased hospitalization rates. Severe depression and anxiety were associated with worse glycemic control and more frequent hospital admissions. Conclusion: Psychological disorders, particularly depression and anxiety, are highly prevalent in patients with diabetes and heart failure. These disorders are significantly associated with worse heart function, poorer glycemic control, and higher hospitalization rates. These findings underscore the importance of integrated care approaches that address both physical and psychological health in this patient population. Early screening and management of psychological disorders may improve clinical outcomes and quality of life in diabetic patients with heart failure. Keywords: Diabetes Mellitus, Heart Failure, Psychological Disorders, Depression, Anxiety, Left Ventricular Ejection Fraction, HbA1c.